Kajian Fisika Kimia Perairan Danau Bangkau Sebagai Dasar Pengembangan Budidaya Ikan - Siswanto, Siswanto; Sofarini, Dini; Hanifa, Marissa Septa (Universitas Trunojoyo Madura, 2021)
Nowadays, in the Danau Bangkau swamp, there is a tendency that some types of fish are increasingly difficult to find and the size of the fish that are still available is relatively small, and the catch of fishermen has decreased. Utilization of fishery potential of Danau Bangkau swamp through the development of aquaculture business is an alternative option that must be implemented. This research was conducted to be able to see the feasibility of the water quality in the Danau Bangkau swamp so that hope it can be basic information for the development of aquaculture in that area. The results showed that the temperature range in the waters of the Danau Bangkau swamp was 28.3-32.4 oC, the brightness was 72-95 cm, degree of acidity (pH) is 6.01-7.2, dissolved oxygen (DO) 1.2-4.3 mg/l, nitrate 0.7-9.8 mg/l, phosphate 0.2-3.31 mg/l and total suspended solids 7-48 mg/l. In general, the value of water quality parameters fulfill the quality standards, except for dissolved oxygen and phosphate parameters. The low levels of dissolved oxygen and high levels of phosphate indicated that there has been pollution in the Danau Bangkau swamp waters so it is not suitable for the cultivation activities.